Banking system reform, earnings quality and credit allocation - Xiuli Zhu; Lianjun Li; Yunkui Xue (China Journal of Accounting Research, 2012)
This paper investigates credit allocation before and after the 2003 banking system reform in China. We find that relationships between earnings quality and new short-term loans, long-term loans and total loans in listed companies changed significantly after the banking system reform, especially in state-owned listed companies. Further investigation shows that due to the influence of rent-seeking, banks have eased the earnings requirements of non-state-owned listed companies. These findings enhance our understanding of the economic consequences of the banking system reform and of credit discrimination under the new regime.
Keywords: G3; G32; G38; 650; Banking system reform; Ownership; Earnings quality; Credit allocation